Most Generous Lord Bishop, by Mercury Blest. John of the Lithuanian Dukes – Patron of the Arts and Sciences - Rowell, S. C. (Senoji Lietuvos literatūra, 2020)
Sigismund the Old’s illegitimate son John of the Lithuanian Dukes was a well educated Renaissance prince, a conscientious bishop and administrator, a competent secular landowner (the count of Šiauliai and Januszpol) and warlord. He succeeded in creating infrastructure for fashionable art and architecture. He sponsored theologians and men of letters at his court and exploited the most modern means – the printed word and image, neo-Latin occasional poetry to promote and publicise his interests. In Vilnius he issued the first codex of local canon law and had it printed in a fashionable edition in Cracow with details confirming his status as a royal bishop and promotor of the cult of the Jagiellonian dynastic saint – his half-uncle Casimir. The 1528 Vilnius Diocesan Statutes appeared a year before the First Lithuanian Statute of civil laws. After he became bishop of Poznań in 1536 he worked with local clergy to publish a church calendar (Rubricella) for 1538 which bore his Pogoń/Vytis coat of arms with a panegyrical epigram. That year he issued a charter and gave money for the publication of a new book of hours for his cathedral and diocese which also included a dedicatory verse and his new coat of arms which combined the Pogoń/Vytis emblem with the Columns of Gediminas. Unfortunately, that same year John died from the effects of quaternary fever (a malaria-related disease) before his career in the Crown of Poland could develop further.
Keywords: John of the Lithuanian Dukes; bishop of Vilnius; patronage; occasional literature